2015
DOI: 10.3390/ijerph13010087
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarettes on Hospital Campuses

Abstract: Smoke and tobacco-free policies on hospital campuses have become more prevalent across the U.S. and Europe, de-normalizing smoking and reducing secondhand smoke exposure on hospital grounds. Concerns about the increasing use of electronic cigarettes (e-cigarettes) and the impact of such use on smoke and tobacco-free policies have arisen, but to date, no systematic data describes e-cigarette policies on hospital campuses. The study surveyed all hospitals in North Carolina (n = 121) to assess what proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Eleven studies described ENDS policies enacted at the local, 775,776 state, 776780 and country level 781784 ; others addressed proposed city policies, 785 university policies, 786 public and stakeholder opinion of ENDS policies, 334,340,343,351,354,357,374,392,398,399,443,452,469,484,485,717,787794 the unmet research needs of state and community tobacco control practitioners regarding ENDS, 795 implementation and enforcement of ENDS policies in hospitals, 796 and policies related to vaping on American transit systems. 797 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…Eleven studies described ENDS policies enacted at the local, 775,776 state, 776780 and country level 781784 ; others addressed proposed city policies, 785 university policies, 786 public and stakeholder opinion of ENDS policies, 334,340,343,351,354,357,374,392,398,399,443,452,469,484,485,717,787794 the unmet research needs of state and community tobacco control practitioners regarding ENDS, 795 implementation and enforcement of ENDS policies in hospitals, 796 and policies related to vaping on American transit systems. 797 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…These findings suggest that local or state regulations controlling secondhand exposure to vapor of e-cigarettes in public places (eg, school buildings, stores, restaurants, school grounds, parks) will be a useful strategy. Multiple states, localities, and health organizations have already banned use of these products in public settings where cigarette smoking is prohibited ( 25 ), including hospitals ( 26 ). However, other states have drafted laws in which e-cigarettes are excluded from the definitions of tobacco products or smoking, which could undermine regulation ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Often, policies are determined at a local level by local governments, companies or institutions, resulting in varying approaches. 22–24 Previous surveys, one from Spain, the others from the USA, have assessed support for restrictions on use of e-cigarettes in enclosed public places or areas where smoking is not allowed. 12 13 25–29 They generally found that those who had used or tried e-cigarettes, as well as smokers, were less supportive of restrictions.…”
Section: Introductionmentioning
confidence: 99%